A biochemical multi-species quality model of a drinking water distribution system for simulation and design - Arminski, Krzysztof; Zubowicz, Tomasz; Brdyś, Mieczysław A. (Zielona Góra: Uniwersytet Zielonogórski)
Drinking Water Distribution Systems (DWDSs) play a key role in sustainable development of modern society. They are classified as critical infrastructure systems. This imposes a large set of highly demanding requirements on the DWDS operation and requires dedicated algorithms for on-line monitoring and control to tackle related problems. Requirements on DWDS availability restrict the usability of the real plant in the design phase. Thus, a proper model is crucial.
Keywords: multi-species; chloramine; quality; drinking water distribution system; critical infrastructure system